Tuning thermal conductivity in molybdenum disulfide by electrochemical intercalation - Gaohua Zhu (Nature Portfolio, 2016)
Molybdenum disulfide shows potential for use in nanoelectronics and optoelectronics. Here, the authors use electrochemical intercalation to tune its structural and compositional features, and show that the thermal conductivity can be effectively modified over a considerable range.